Existence of solutions of fractional boundary value problems with p-Laplacian operator - Mahmudov, Nazim I.; Unul, Sinem (Springeropen, 2015)
In this paper, the existence of the solutions of the fractional differential equation with p-Laplacian operator and integral conditions is discussed. By Green's functions and the fixed point theorems, we state and prove the existence and uniqueness results of the problem. Two examples are given to illustrate the results.
Keywords: existence and uniqueness; fractional calculus; p-Laplacian